How To Motivate Students Through mining Educational Data - Hachem Alaoui Haroun, Moulay; Hachem, El-Kaber; Ziti, Cherif; Bassiri, Mustapha (International Journal of Engineering and Technology, 2018)
Despite having educational data mining as a new research area, it has already made contributions to the learning theories and their teaching practices. The aims of this article are to present a way of improving both the student and the teacher performance, and to empower educational institutions through exploring data and through examining them with the purpose of motivating students in different aspects of their performance.Â Â